Investigation on thermal response in fretting sliding with the consideration of plastic dissipation, surface roughness and wear - Shen, Fei (2020)
This study investigates the thermal response of titanium alloy fretting sliding through a numerical approach with the consideration of the friction dissipation, plastic dissipation, surface roughness and wear. The fretting sliding of a cylindrical pad on a specimen with surface roughness is modeled to predict the temperature distribution, the evolution of the wear profile, and the fields of surface and subsurface stresses. Specifically, a thermo-elasto-plastic constitutive model considering the thermal-induced softening of material properties is developed to evaluate the contact pressure and the tangential stress on the surfaces as well as the subsurface stresses in the contacting components. The friction and plastic energy dissipations function together as the heat source to cause the temperature rise in the contact zone. A modified Archard model is used to predict the wear profile of the contact surface and change the contact geometry. The models are then incorporated in the finite element analysis of the fretting sliding to evaluate the thermal response. The influences of the plastic dissipation and the surface roughness on the temperature rise in the fretting sliding are discussed.